GUGAT CERAI: MEMBEBASKAN PREMPUAN DARI PENDERITAAN - Nurmala Fahriyanti (QAWWAM, 2019)
In Mataram West Nusa Tenggara, people is lives are regulated on daily basis by religious law, traditional (adat) law and state law. To understand these complex cultural and religious processes as they affect women in particular, I will examine the issue of divorce, also known as sue divorce. This tipe of divorce is socially-sanctioned. I will focus my examination in Mataram, an city of Lombok West Nusa Tenggara. In Lombok society marriage constitutes an important part of the life cycle. Someone is not considered an adult until marriage. Marriage is not only united two individual, but also united two families. However this dream canot be realized over the long term. If family problems arise and there are no suitable solutions, people may choose to divorce. For instance, if a wife unable to fulfill her obligations as a wife, her husband can divorce her by verbal means alone, according to any of the three existing legal systems (religious customary or state law). By contrast, if her husband unable to fulfill her obligations as a husband his wife can divorce him in only one way by making an application to Islamic Court to do divorce. In marriage available successful couple builds the family that sakinah, mawaddah and warahmah. But then available also that unsuccessful and end with separate or divorce. Separate constitutes a thing that often happens deep good human life divorce the initiating from the husband and also divorce the initiating from the wife, that its cause islamic law puts attention that adequately significant to that thing. It can appear if understand about islamic law, undoubtedly will find both of previous thing and its terminological islamic law. There is no divorce without started by marriage. But upon that aim not attained, therefore divorce constitutes last way out that must been sailed through. Divorce can't be done but there is grounds which corrected by religion, adat and state law. In islamic law, that divorce grounds experience developing according to social development. Basically islamic law establishes that divorce reason which is wrangle which really culminates and jeopardize the so called soul safety with “ syiqaq ”. Intention is if worried a couple its happening dispute (dispute not only means wrangle among husband or wife can also distinctive principle and opinion) therefore delegate a someone of its husband family and a someone of wife family. And if both of wife and husband will goodness and they can make resolution and look for the solution, but if there are suitable solution wife or husband can do divorce.